Złotnicy we Wschowie w XVII i pierwszej połowie XVIII wieku w świetle dokumentów źródłowych = Goldsmiths in Wschowa in the 17th and the first half of the 18th century in the light of archival documents - Łyczak, Bartłomiej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Wschowa (ger. Fraustadt) is located in southern part of Greater Poland. During the 17th and the first half of the 18th century it was situated right by the border between the Polish-Lithuanian Commonwealth and Silesia, which stayed under control of the Habsburgs until 1740, when it became a part of Prussia. Until now the knowledge on the topic of goldsmiths active in that centre was mainly based on studies made before the Second World War. An archival research, mostly conducted in the National Archive in Zielona Góra, led to discovering of many new, hitherto unknown information.
Keywords: Wschowa; złotnicy; źródła historyczne; goldsmiths; source documents